Improving mobile payment adoption among Gen Z in Indonesia: An extended of technology acceptance model and Delone and McLean information system success model - Rosnidah, Ida; Johari, Razana Juhaida; Sulistyowati, Wiwit Apit (Edelweiss Applied Science and Technology, 2025)
This study develops TAM with system quality and service quality that individuals consider when using online financial services. The development of online financial transactions has increased every year, but the adoption of mobile payments has not been optimized. These conditions motivate this study to predict the factors that drive Gen Z’s interest in adopting mobile banking for processing financial transactions or online payments. The objective of this study was to extend TAM with system quality and service quality that individuals consider when using online financial services. This study uses a survey method by distributing questionnaires to Gen Z regarding their intention to use mobile payments. 235 valid data points were processed using Structural Equation Modeling through Smart PLS. The findings show that Gen Z focuses on the ease and benefits of mobile payment services, while system quality and service quality are not the main considerations. This implies that for current financial service users, aspects such as convenience and immediate benefits are more dominant in shaping positive attitudes toward new technologies. Therefore, service providers should prioritize improving intuitive interface design and clear communication about the benefits of their products to encourage adoption.